2017
DOI: 10.1111/hdi.12533
|View full text |Cite
|
Sign up to set email alerts
|

Native arteriovenous fistula placement in three patients after implantation of a left ventricular assist device with non‐pulsatile blood flow

Abstract: Patients with left ventricular assist device have an increased risk for postoperative acute kidney injury and long-term requirement of dialysis. As a chronic access for dialysis, native arteriovenous fistulae are uncommon options due to suspected maturation failure. We present three patients who received successful arteriovenous fistulae placement after left ventricular assist device implantation with assisted long term patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Definition and classification of cardiorenal syndromes (28) Cardiorenal syndromes general definition: Disorders of the heart and kidneys whereby acute or chronic dysfunction in one organ may induce acute or chronic dysfunction of the other. the AVFs functioned well (41). In our opinion, AVFs can be used successfully in patients with continuous flow LVADs.…”
Section: Second Can Arteriovenous Fistulas Mature Without Pulsatile mentioning
confidence: 55%
“…Definition and classification of cardiorenal syndromes (28) Cardiorenal syndromes general definition: Disorders of the heart and kidneys whereby acute or chronic dysfunction in one organ may induce acute or chronic dysfunction of the other. the AVFs functioned well (41). In our opinion, AVFs can be used successfully in patients with continuous flow LVADs.…”
Section: Second Can Arteriovenous Fistulas Mature Without Pulsatile mentioning
confidence: 55%
“…Arteriovenous hemodialysis accesses, which divert a significant portion of the cardiac output from systemic perfusion and have been implicated in high‐output HF, have been a cause for concern, both in terms of whether maturation would occur for arteriovenous fistulas, and whether systemic perfusion would remain adequate 33, 34. Recent case reports have described successful arteriovenous fistulas maturation in hemodialysis patients with LVADs 35, 36. A large proportion of our patients had arteriovenous accesses at time of VAD implantation, but we were unable to investigate outcomes related to dialysis access because of limited numbers.…”
Section: Discussionmentioning
confidence: 99%
“…6 While the lack of pulsatility was theorized to lead to uncertainty of fistula maturation in the setting of continuous flow support, several authors have reported long-term success in this setting with excellent AVF maturation for use in dialysis. [8][9][10] Now, Hair and colleagues 7 also confirm that AVF can be successfully matured in a circulation supported by a TAH with mechanically induced pulsatile flow. It is, however, important to note that the shunt created by a mature AVF may reach 600 to 1200 mL/min, 4 and the risk of elevating pulmonary vascular resistance should be factored into the decision to pursue an AVF in a bridge-to-transplant candidate.…”
mentioning
confidence: 87%